Epigenetic Inactivation of Acetyl-CoA Acetyltransferase 1 Promotes the Proliferation and Metastasis in Nasopharyngeal Carcinoma by Blocking Ketogenesis - Lu, Yunliang; Zhou, Xiaohui; Zhao, Weilin; Liao, Zhipeng; Li, Bo; Han, Peipei; Yang, Yanping; Zhong, Xuemin; Mo, Yingxi; Li, Ping; Huang, Guangwu; Xiao, Xue; et al. (Frontiers in Oncology, 2021)
The dysregulation of epigenetic modification and energy metabolism cooperatively contribute to the tumorigenesis of nasopharyngeal carcinoma (NPC). However, the detailed mechanisms underlying their joint contribution to NPC development and progression remain unclear. Here, we investigate the role of Acy1 Coenzyme A Acyltransferases1 (ACAT1), a key enzyme in the metabolic pathway of ketone bodies, in the proliferation and metastasis of NPC and to elucidate the underlying molecular mechanisms. Ketogenesis, plays a critical role in tumorigenesis. Previously, we reported two enzymes involved in ketone body metabolism mediate epigenetic silencing and act as tumor suppressor genes in NPC. Here, we identify another key enzyme, Acetyl-CoA acetyltransferase 1 (ACAT1), and show that its transcriptional inactivation in NPC is due to promoter hypermethylation. Ectopic overexpression of ACAT1 significantly suppressed the proliferation and colony formation of NPC cells in vitro. The migratory and invasive capacity of NPC cells was inhibited by ACAT1. The tumorigenesis of NPC cells overexpressing ACAT1 was decreased in vivo. Elevated ACAT1 in NPC cells was accompanied by an elevated expression of CDH1 and a reduced expression of vimentin and SPARC, strongly indicating that ACAT1 is involved in regulating epithelial-mesenchymal transition (EMT). We also found that ACAT1 contributes to increased intracellular levels of β-hydroxybutyrate (β-HB). Exogenously supplied β-HB significantly inhibits the growth of NPC cells in a dose-dependent manner. In summary, ACAT1 may function as a tumor suppressor via modulation of ketogenesis and could thus serve as a potential therapeutic target in NPC. In summary, our data suggest that regulation of ketogenesis may serve as adjuvant therapy in NPC.